Visualizing cityscapes of classical antiquity : from early modern reconstruction drawings to digital 3D models : with a case study from the ancient town of Koroneia in Boeotia, Greece /: from early modern reconstruction drawings to digital 3D models : with a case study from the ancient town of Koroneia in Boeotia, Greece. (2018) - Piccoli, Chiara
No abstract available